Novel Roles of Small Extracellular Vesicles in Regulating the Quiescence and Proliferation of Neural Stem Cells - Zhang, Jingtian; Uchiyama, Junki; Imami, Koshi; Ishihama, Yasushi; Kageyama, Ryoichiro; Kobayashi, Taeko (Frontiers in Cell and Developmental Biology, 2021)
Neural stem cell (NSC) quiescence plays pivotal roles in avoiding exhaustion of NSCs and securing sustainable neurogenesis in the adult brain. The maintenance of quiescence and transition between proliferation and quiescence are complex processes associated with multiple niche signals and environmental stimuli. Exosomes are small extracellular vesicles (sEVs) containing functional cargos such as proteins, microRNAs, and mRNAs. The role of sEVs in NSC quiescence has not been fully investigated. Here, we applied proteomics to analyze the protein cargos of sEVs derived from proliferating, quiescent, and reactivating NSCs. Our findings revealed fluctuation of expression levels and functional clusters of gene ontology annotations of differentially expressed proteins especially in protein translation and vesicular transport among three sources of exosomes. Moreover, the use of exosome inhibitors revealed exosome contribution to entrance into as well as maintenance of quiescence. Exosome inhibition delayed entrance into quiescence, induced quiescent NSCs to exit from the G0 phase of the cell cycle, and significantly upregulated protein translation in quiescent NSCs. Our results suggest that NSC exosomes are involved in attenuating protein synthesis and thereby regulating the quiescence of NSCs.